Intraoperative Tobramycin Powder Prevents Enterobacter cloacae Surgical Site Infections in a Rabbit Model of Internal Fixation. Issue 1 (January 2021) - Brao, Kristen; Greenwell, Patrick; Hsu, Kuei Ling; Marinos, Dimitrius; Stains, Joseph P.; Hovis, James P.; Joshi, Manjari; Shirtliff, Mark E.; O'Toole, Robert V.; Harro, Janette M.
Abstract : Objectives: To evaluate the efficacy of intraoperative tobramycin powder in preventing surgical site infection (SSI) and implant colonization with Enterobacter cloacae in a rabbit fixation model. Gram-negative rods, particularly Enterobacter species, comprise an increasing percentage of SSI at our institution. Methods: Eighteen New Zealand White rabbits underwent surgical fixation of the left tibia with implantation of a plate and screws. The surgical site and implant were inoculated with 1 × 10 7 CFUs E. cloacae. The selected E. cloacae isolate was resistant to tobramycin and capable of forming biofilms. Nine rabbits received 125 mg tobramycin powder directly into the surgical site, overlying the implant. The control group was untreated. Fourteen days postinfection, the tibiae and implants were explanted. Radiographs were taken with and without the implants in place. One tibia from each group was examined after hematoxylin and eosin staining. The remaining tibiae and implants were morselized or sonicated, respectively, and plated on agar to determine infection burden. Data were analyzed with Fisher exact tests and Mann–Whitney U tests. Results: No bone infection or implant colonization occurred in the tobramycin-treated group. In the control group, 7 of 8 rabbits developed bone infections ( P = 0.001), and 4 of 8 implants were colonized ( P = 0.07). No gross disruption of the normal bone architecture was observed in either group. Conclusions: Intraoperative tobramycin powder applied at the time of contamination prevented bone infection with E. cloacae in this rabbit fixation model. The results are encouraging because the E. cloacae isolate was tobramycin-resistant, demonstrating the utility of intraoperative powdered antibiotics. Abstract : Supplemental Digital Content is Available in the Text.